Scalable, thin asymmetric composite solid electrolyte for high‐performance all‐solid‐state lithium metal batteries. Issue 3 (5th July 2022) - Wang, Guoxu; Liang, Yuhao; Liu, Hong; Wang, Chao; Li, Dabing; Fan, Li‐Zhen
Abstract: All‐solid‐state Li metal batteries (ASSLMBs) have been considered the most promising candidates for next‐generation energy storage devices owing to their high‐energy density and safety. However, some obstacles such as thick solid electrolyte (SSEs) and unstable interface between the solid‐state electrolytes (SSEs) and the electrodes have restricted the practical application of ASSLBs. Here, the scalable polyimide (PI) film reinforced asymmetric ultra‐thin ( 20 μm) composite solid electrolyte (AU‐CSE) with a ceramic‐rich layer and polymer‐rich layer is fabricated by a both‐side casting method and rolling process. The ceramic‐rich layer not only acts as a "securer" to inhibit the lithium dendrite growth but also redistributes Li‐ions uniform deposition, while the polymer‐rich layer improves the compatibility with cathode materials. As a result, the obtained AU‐CSE demonstrates an ionic conductivity of 1.44 × 10 −4 S cm −1 at 35°C. The PI‐reinforced AU‐CSE enables Li/Li symmetric cell stable cycling over 1200 h at 0.2 mA cm −2 and 0.2 mAh cm −2 . Li/LiNi0.6 Co0.2 Mn0.2 O2 and Li/LiFePO4 ASSLMBs achieve superior performances at 35°C. This study provides a new way of solving the interface problems between SSEs and electrodes and developing high‐energy‐density ASSLMBs for practical applications. Abstract : An asymmetric ultra‐thin composite solid electrolyte with ceramic‐ and polymer‐rich layers was constructed to simultaneously overcome the lithium dendrite growth on the anode side and the large resistance on the cathode side.